Atomic Nuclei From Quantum Monte Carlo Calculations With Chiral EFT Interactions - Gandolfi, Stefano; Lonardoni, Diego; Lovato, Alessandro; Piarulli, Maria (Frontiers in Physics, 2020)
Quantum Monte Carlo methods are powerful numerical tools to accurately solve the Schrödinger equation for nuclear systems, a necessary step to describe the structure and reactions of nuclei and nucleonic matter starting from realistic interactions and currents. These ab-initio methods have been used to accurately compute properties of light nuclei – including their spectra, moments, and transitions – and the equation of state of neutron and nuclear matter. In this work we review selected results obtained by combining quantum Monte Carlo methods and recent Hamiltonians constructed within chiral effective field theory.